Serum Amyloid A Stimulates Vascular and Renal Dysfunction in Apolipoprotein E-Deficient Mice Fed a Normal Chow Diet - Chami, Belal; Hossain, Farjaneh; Hambly, Thomas W.; Cai, Xiaoping; Aran, Roshanak; Fong, Genevieve; Vellajo, Abigail; Martin, Nathan J.J; Wang, XiaoSuo; Dennis, Joanne M.; Sharma, Arpeeta; Shihata, Waled A.; et al. (Frontiers in Immunology, 2019)
Elevated serum amyloid A (SAA) levels may promote endothelial dysfunction, which is linked to cardiovascular and renal pathologies. We investigated the effect of SAA on vascular and renal function in apolipoprotein E-deficient (ApoE-/-) mice. Male ApoE-/- mice received vehicle (control), low-level lipopolysaccharide (LPS) or recombinant human SAA by i.p. injection every third day for 2 weeks. Heart, aorta and kidney were harvested between 3 days and 18 weeks after treatment. SAA administration increased vascular cell adhesion molecule (VCAM)-1 expression and circulating monocyte chemotactic protein (MCP)-1 and decreased aortic cyclic guanosine monophosphate (cGMP), consistent with SAA inhibiting nitric oxide bioactivity. In addition, binding of labelled leukocytes to excised aorta increased as monitored using an ex vivo leukocyte adhesion assay. Renal injury was evident 4 weeks after commencement of SAA treatment, manifesting as increased plasma urea, urinary protein, oxidized lipids, urinary kidney injury molecule (KIM)-1 and multiple cytokines and chemokines in kidney tissue, relative to controls. Phosphorylation of nuclear-factor-kappa-beta (NFB-p-P65), tissue factor (TF) and macrophage recruitment increased in kidneys from ApoE-/- mice 4 weeks after SAA treatment, confirming that SAA elicited a pro-inflammatory and pro-thrombotic phenotype. These data indicate that SAA impairs endothelial and renal function in ApoE-/- mice in the absence of a high-fat diet.